Research Progress of Bacteriocin Combined with Physical Technology in the Prevention and Control of Foodborne Pathogens and Spoilage Microorganisms - Mingzhu WANG; Zihao TIAN; Zhongmei TAN; Jie REN; Gaoyun WU; Jinqi GUO; Yuchang YAO; Yuan YIN; Bailiang LI; Jiage MA; Wei YU (Shipin gongye ke-ji)
Food safety issues caused by foodborne pathogens and spoilage microorganisms have become one of the public health challenges worldwide. Bacteriocins are antimicrobial peptides synthesized by some bacterial ribosomes and are widely used as bio-preservatives and food additives. However, bacteriocins may have some limitations when used individually, such as the narrow inhibitory spectrum and easy degradation by enzymes. Previous studies found that the combined use of bacteriocins and physical technologies may exhibit synergistic antimicrobial effects. This strategy could effectively expand the range of antimicrobial activity, enhance the antimicrobial effect, and prolong the shelf life of food, thereby ensuring food safety and human health. This paper reviews the synergistic antimicrobial strategies and mechanisms of bacteriocins in combination with physical technologies, including ultrasonic treatment, high-pressure treatment, heat treatment, pulsed electric field, and nanotechnology. Meanwhile, the influence of the combination of bacteriocins and physical technologies on food quality and safety is elaborated. Moreover, the development trend and application prospect of the antimicrobial strategy are discussed. The aim of this review is to provide the theoretical support and reference basis for the industrial application of bacteriocins combined with physical technologies to inhibit foodborne pathogens and spoilage microorganisms.